Thyroid function and associated mood changes after COVID-19 vaccines in patients with Hashimoto thyroiditis - Ma, Yifei; Zeng, Jiling; Jiang, Yongluo; Xu, Yi-Wei; Wang, Youlong; Zhong, Guanqing; Liu, Nianqi; Wang, Yanqi; Zhang, Zhiying; Li, Yiming; Chen, Shuqin; Wei, Xiao-Long; et al. (Frontiers in Immunology, 2023)
Context SARS-CoV-2 (COVID-19) vaccines may incur changes of thyroid functions followed with mood changes, and Hashimoto thyroiditis (HT) patients were suggested to bear higher risk. Objective We primarily aim to find whether COVID-19 vaccination could induce potential subsequent thyroid function and mood changes. Secondary aim was to find inflammatory biomarkers associated with risk. Methods The retrospective, multi-center study recruited HT patients receiving COVID-19 inactivated vaccines. C-reactive proteins (CRP), thyroid-stimulating hormones (TSH), and mood changes were studied before and after vaccination during a follow-up of 6 months period. Independent association was investigated between incidence of mood state, thyroid functions, and inflammatory markers. Propensity score-matched (PSM) comparisons between vaccine and control group were carried out to investigate difference. Results Final analysis included 2765 HT patients in vaccine group and 1288 patients in control group. In matched analysis, TSH increase and mood change incidence were both significantly higher in vaccine group (11.9% versus 6.1% for TSH increase, and 12.7% versus 8.4% for mood change incidence). An increase in CRP was associated with mood change (p < 0.01 by Kaplan-Meier method) and severity (r = 0.75) after vaccination. Baseline CRP, TSH, and Antibodies of thyroidal peroxidases (anti-TPO) were found to predict incidence of mood changes. Conclusions COVID-19 vaccination seemed to induce increased levels and incidence of TSH surge followed by mood changes in HT patients. Higher levels of pre-vaccine serum TSH, CRP, and anti-TPO values were associated with higher incidence in early post-vaccine phase.